2021
DOI: 10.53684/csp.v1i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Ansiedad durante la pandemia COVID-19, en docentes de instituciones educativas del distrito de Yanahuanca en Pasco

Abstract: Objetivos: El objetivo del estudio fue determinar ansiedad durante la pandemia COVID-19, en docentes de instituciones educativas del distrito de Yanahuanca en Pasco.  Materiales y métodos: El enfoque de este estudio fue el cuantitativo y su diseño metodológico el descriptivo y transversal. La población estuvo conformada por 353 docentes de una red de instituciones educativas en Yanahuanca-Pasco. La técnica utilizada fue la encuesta y el instrumento de medición fue la Escala de Ansiedad por Coronavirus o Corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…For Vento et al (2021), the concept of anxiety in the era of the COVID-19 pandemic implies worry, fear, apprehension, doubts and anxiety that, if frequent, would affect the normal physical and psychological performance of the individual. It has been found that students who work online show greater levels of anxiety related to uncertainty and depression, which could be due to the sense of loneliness that they experience.…”
Section: Computer Anxiety -Psychological Distressmentioning
confidence: 99%
“…For Vento et al (2021), the concept of anxiety in the era of the COVID-19 pandemic implies worry, fear, apprehension, doubts and anxiety that, if frequent, would affect the normal physical and psychological performance of the individual. It has been found that students who work online show greater levels of anxiety related to uncertainty and depression, which could be due to the sense of loneliness that they experience.…”
Section: Computer Anxiety -Psychological Distressmentioning
confidence: 99%